From conventional to self-ligating bracket systems: Is it possible to aggregate the experience with the former to the use of the latter? - Anderson Capistrano; Aldir Cordeiro; Danilo Furquim Siqueira; Leopoldino Capelozza Filho; Mauricio de Almeida Cardoso; Renata Rodrigues de Almeida-Pedrin (Dental Press Journal of Orthodontics, 2014)
INTRODUCTION: Orthodontics, just as any other science, has undergone advances in technology that aim at improving treatment efficacy with a view to reducing treatment time, providing patients with comfort, and achieving the expected, yet hardly attained long-term stability. The current advances in orthodontic technology seem to represent a period of transition between conventional brackets (with elastic ligatures) and self-ligating brackets systems. Scientific evidence does not always confirm the clear clinical advantages of the self-ligating system, particularly with regard to reduced time required for alignment and leveling (a relatively simple protocol), greater comfort for patients, and higher chances of performing treatment without extractions - even though the number of extractions is more closely related to patient's facial morphological pattern, regardless of the technique of choice. Orthodontics has recently and brilliantly used bracket individualization in compensatory treatment with a view to improving treatment efficacy with lower biological costs and reduced treatment time. OBJECTIVE: This paper aims at presenting a well-defined protocol employed to produce a better treatment performance during this period of technological transition. It explores the advantages of each system, particularly with regards to reduced treatment time and increased compensatory tooth movement in adult patients. It particularly addresses compensable Class III malocclusions, comparing the system of self-ligating brackets, with which greater expansive and protrusive tooth movement (maxillary arch) is expected, with conventional brackets Capelozza Prescription III, with which maintaining the original form of the arch (mandibular arch) with as little changes as possible is key to yield the desired results.